2019
DOI: 10.1007/s11151-019-09691-9
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Control and Executive Compensation

Abstract: This article analyzes the trajectory and causes of the explosion of American corporate CEOs' compensation relative to that of average workers between 1958 and 2017. The historical data are presented and analyzed in more detail for 2016 and 2017. Important biases in alternative data sets are explored. Alternative hypotheses for the dramatic changes over time are proposed but not resolved. Among other things, the paper investigates the role of tax and other government policy changes and regulation-induced innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Thus, it can be expected that MPH framework will be more applicable in a banking environment where CG mechanisms are weak. Proponents of this view consider EC arrangements as a product of close interpersonal relationships and negotiations between powerful senior managers, such as CEOs, and weak board of directors (Ntim et al, 2015; Sapp, 2008; Scherer, 2020). This can lead to the creation of inefficient managerial contracts (e.g., Kartadjumena & Rodgers, 2019; Scherer, 2020).…”
Section: Theoretical Framework: Cg Ec and Sbdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be expected that MPH framework will be more applicable in a banking environment where CG mechanisms are weak. Proponents of this view consider EC arrangements as a product of close interpersonal relationships and negotiations between powerful senior managers, such as CEOs, and weak board of directors (Ntim et al, 2015; Sapp, 2008; Scherer, 2020). This can lead to the creation of inefficient managerial contracts (e.g., Kartadjumena & Rodgers, 2019; Scherer, 2020).…”
Section: Theoretical Framework: Cg Ec and Sbdmentioning
confidence: 99%
“…Proponents of this view consider EC arrangements as a product of close interpersonal relationships and negotiations between powerful senior managers, such as CEOs, and weak board of directors (Ntim et al, 2015;Sapp, 2008;Scherer, 2020). This can lead to the creation of inefficient managerial contracts (e.g., Kartadjumena & Rodgers, 2019;Scherer, 2020). The outcome of such contract is the exacerbation of agency conflicts by increasing the disparity of interests between senior managers and stakeholders (Bebchuk & Weisbach, 2010).…”
Section: Theoretical Framework: Cg Ec and Sbdmentioning
confidence: 99%
“…One of the responsibilities of compensation committee members is to establish performance incentive targets in advance (such as return on investment, sales growth rate or market share growth in key markets, etc.). Meeting or exceeding the targets triggers cash or stock dividends, but Scherer (2020) [48] found that company shareholders do become secondary participants in executive compensation issues. But they appear to exert little control over pay levels.…”
Section: Considerations For Designing Incentive Executive Compensationmentioning
confidence: 99%
“…Ma and Jing [24] for instance, in a recent paper, examine the possibility of using the mission of the organization and fixed salaries as substitutes for material incentives in not-for-profit organizations to increase organizational efficiency. Only 50 years ago, a paper like this might have been unconceivable: Incentives were either inexistent or a small percentage of most people's salary, because most people did not believe in them as motivators [25,26]. It seemed that the natural thing to do was to do things 'right' as the reason of everybody's job was to do the 'right' thing and contribute to the organizational goals.…”
Section: Different Concepts Of Managementmentioning
confidence: 99%